Constitutional justice and political process: the tendencies of interaction and search for the doctrine - Egidijus Jarašiūnas (Politologija)
In this article, the problems of the interaction of constitutional justice, which is the main institution of constitutional protection, and the political process are dealt with. At the junction of law and politics, it is very important to define the possible limits of the action of the Constitutional Court and to guarantee that the Court, deciding the constitutionality issues of legal decisions of the institutions of power, should assess their conformity to the Constitution but never whether these decisions were rational or suitable.